Acute effects of fresh versus dried Hayward green kiwifruit on sleep quality, mood, and sleep-related urinary metabolites in healthy young men with good and poor sleep quality - Alexander P. Kanon; Alexander P. Kanon; Alexander P. Kanon; Caroline Giezenaar; Caroline Giezenaar; Nicole C. Roy; Nicole C. Roy; Nicole C. Roy; Warren C. McNabb; Warren C. McNabb; Sharon J. Henare (Frontiers in Nutrition, 2023)
Background and aimsDaily kiwifruit (KF) consumption has been associated with improved sleep quality, but underlying physiological mechanisms are unknown. This study examined acute effects of fresh and dried green KF, compared with a water control, on sleep quality, mood, and urinary serotonin and melatonin metabolite concentrations.Methods24 men (age: 29 ± 1 years, body mass index: 24 ± 1 kg/m2) with poor (n = 12) or good (n = 12) sleep quality participated in a randomized, single-blind crossover study. One of three treatments was consumed with a standardized evening meal; (1) the flesh of two fresh green KF, (2) dried green KF powder (including skin; equivalent to dry matter of two fresh KF) mixed with water, or (3) a water control, in their own home. Subjective and objective sleep quality, mood, waking urinary 5-hydroxyindoleacetic acid (5-HIAA), 6-sulfatoxymelatonin (aMT6s), vitamin C and B-vitamin concentrations were determined.ResultsRegardless of sleep quality group, compared to control, morning sleepiness, alertness upon awakening, and vigor were improved (p < 0.05) after dried KF consumption. Compared to control, both fresh and dried KF treatments tended (p < 0.1) toward improved esteem and total mood disturbance. Both KF treatments increased (fresh +1.56 ± 0.4 ng/g, p = 0.001; dried: +1.30 ± 0.4 ng/g, p = 0.004) urinary concentration of the serotonin metabolite 5-HIAA compared to the control (4.32 ± 0.4 ng/g). In poor sleepers, ease of awakening improved by 24% after dried KF consumption (p = 0.005) and tended to improve by 13% after fresh KF intake (p = 0.052) compared to the control. Good sleepers tended toward 9% improved ratings of getting to sleep with fresh KF (p = 0.053) compared to the control. Poor sleepers had lower amounts of some B-vitamins compared to good sleepers (p < 0.05).ConclusionConsumption of dried or fresh KF with a standard evening meal, was associated with improved aspects of sleep quality and mood, possibly mediated through changes in serotonin metabolism.Clinical trial registration[www.anzctr.org.au], identifier [ACTRN12621000046808].Graphical Abstract